RANCANGAN DEKORATIF SIMETRIS BERDASARKAN MODEL FRAKTAL POLA SIERPINSKY GASKET ASIMETRIS - Nisrina Eka Anadhiya; Eka Nur aini Mulyaningsih; Siti Nur (STKIP PGRI Situbondo, 2024)
A symmetrical decorative design is always attractive to be used in many decoration needs. Fractal model gives a simple way in designing a decorative design that can be recycled later to have other design products easily and efficiently. The iterated function system fractal model used the code that can be modified by affine transformation operation. Sierpinsky gasket is one of a simple but attractive fractal object.